Дослідження енергоефективності машин вторинного очищення посівного зерна - Постнікова, Марина Вікторівна; Постникова, Марина Викторовна; Postnikova, Marina (My University, 2021)
UK: В якості типового представника машин вторинного очищення посівного зерна представлена машина СВУ-5А. В роботі були проаналізовані режими роботи електропривода робочої машини та технологічні вимоги до очищення посівного зерна. Вперше для визначення оптимальних умов очищення зерна був використаний багатофакторний математичний експеримент, що дозволило при невеликій кількості дослідів провести дослідження і дати рекомендації по удосконаленню робочої машини і керуванню технологічним процесом очищення зерна. Вперше в результаті обробки матриць плану було отримано рівняння регресії для розрахунку спожитої потужності робочої машини в залежності від режимних та конструктивних параметрів. Результати проведених досліджень дозволили розробити рекомендації щодо реалізації енергозберігаючих режимів роботи, що дозволить економити 8-10 % електроенергії. EN: Research of energy efficiency of machines of flow lines of cleaning of sowing grain is an important priority in modern conditions. Problems related to energy efficiency continue to be relevant. One option for a partial solution to this problem is to study the nature of the relationship between the energy performance of the process equipment of grain cleaning lines. The SVU-5A machine is presented as a typical representative of machines of secondary cleaning of sowing grain. The modes of operation of the electric drive of the working machine and technological requirements for cleaning of sowing grain were analyzed in the work. The analysis of ways to reduce energy consumption during grain cleaning took into account the influence of mode and design parameters of the working machine on energy consumption. In this regard, there is a need for research to determine the rational mode and design parameters of the working machine and the choice of power of the drive motor and the optimal transmission efficiency. For the first time, a multifactor mathematical experiment was used to determine the optimal conditions for grain cleaning, which allowed for a small number of experiments to conduct research and make recommendations for improving the working machine and control the technological process of grain cleaning. For the first time, as a result of processing the matrices of the plan, a regression equation was obtained to calculate the power consumption of the working machine depending on the mode and design parameters. The results of the research allowed to develop recommendations for the implementation of energy-saving modes of operation, which will save 8-10 % of electricity. RU: Типичным представителем машин вторичной очистки посевного зерна является машина СВУ-5А. В работе были проанализированы режимы работы электропривода и технологические требования к очистке посевного зерна. Впервые для определения оптимальных условий очистки зерна был использован многофакторный математический эксперимент, что позволило при небольшом количестве опытов провести исследования и дать рекомендации по совершенствованию рабочей машины и управлению технологическим процессом очистки зерна. Впервые в результате обработки матриц плана было получено уравнение регрессии для расчета потребляемой мощности рабочей машины в зависимости от режимных и конструктивных параметров. Результаты проведенных исследований позволили разработать рекомендации по реализации энергосберегающих режимов работы, что позволит экономить 8-10 % электроэнергии.
Energy efficiency research second cleaning machines of sowing grain
Исследование энергоэффективности машин вторичной очистки посевного зерна
Keywords: енергозбереження; раціональне використання електроенергії; економія електроенергії; багатофакторний експеримент; зерноочисний агрегат; energy saving; rational use of electricity; energy saving; multifactor experiment; grain cleaning unit; энергосбережение; рациональное использование электроэнергии; экономия электроэнергии; многофакторный эксперимент; зерноочистительный агрегат